Financial Leverage and Its Impact on Investment Decisions: A Study of Selected Trading Companies in Sri Lanka - Pratheepkanth, P. (South Eastern University of Sri Lanka, 2011)
This research paper primarily focuses on the impact of financial leverage on investment decisions of firms and it is an attempt to look at the impact of financial leverage on investment levels using firm-level panel data in Sri Lanka, researcher expect to contribute to the existing literature by bringing evidence from a plate data set, which comprises 20firms, all listed on the Colombo Stock exchange sampled over a lOyear-period (that is (i.e. from 2000-2009). In addition, researcher distinguishes between two types of firms, namely: (i) high-augmentation firms; and (ii) low augmentation firms. The results reveal a significant negative relationship between leverage and investment More interestingly, while researcher found a negative relationship between leverage and investment for low augmentation firm, our econometric results reveal an insignificant relationship between the two variables for high augmentation firm
Keywords: Financial Leverage; Investment; Trading Companies